A memory exchange hub: encapsulating memory through an architectural intervention - Janse van Rensburg, Nico (University of the Free State, 2021)
This dissertation is an exploration and design of a Memory Exchange Hub in Lephalale in between the Maroela Old Age Home and the local Lephalale Library. Lephalale is situated in Limpopo where the EXXARO coal mine is crucial to South Africa’s energy production and in being so offers a resource for the community at large, but the question is what this industry offers to Lephalale in return. The community is need of an intervention which contributes to their daily routines in community engagement. The reason for this study is to provide a central space in Lephalale for the community to expand their knowledge on different topics and be closely exposed to different types of people in Lephalale. A variety of trees surround the Bushveld landscape and the most important to the people is what is known as the big five South- African trees. These trees forms part of the way Lephalale treats This project introduces the formulation of a theoretical approach through an ancestral dream of the author. This evokes a study on the history of the people of Lephalale and ultimately formulates forms of memory to be introduces as physical realness. A culmination of conceptual approaches like preservation, interweaving and transience influences the design approach. The main theoretical stance is based on the theme of different forms of memory and how memory relates to space and time. A contribution to sustainable building design in a hot interior area is designed using the primary structural use of eucalyptus poles, secondary use of steel and an introduction of an alternate use of material. Thatch roofs evolve into thatch walls as a new morphological element. The main theme of the project introduces a space where the people of Lephalale can engage in different forms of narrative and be reminded of the connection they have with each other, their set of skills and the history of Lephalale.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2021
Keywords: Gathering; Memory; Hermeneutics; Historic; Sustainable; Design; Memory exchange hub